Pre‐Schoolers' Vision for Liveable Cities: Creating 'Care‐Full' Urban Environments. (25th August 2020) - Ergler, Christina R.; Freeman, Claire; Guiney, Tess
Abstract: Although children of all ages have the right to participate in urban planning projects, pre‐literate children's voices are absent from urban debates. In this paper, we explore pre‐schoolers' experiences in, and expectations for, their city by drawing on a participatory research project that used neighbourhood walks and a tile‐based mapping exercise. Findings suggest that young children, although largely absent from planning, policy or child‐friendly city discourses, nonetheless, deeply engage with and value their city and its human and non‐human inhabitants. In our study pre‐schoolers from Dunedin, New Zealand created an urban environment which cares for their citizens by being safe, socially and physically connected and has destinations, amenities and services available for all ages and abilities. We argue in this paper that pre‐schoolers created not only cities based on their own experiences, but 'care‐full' cities that ensure the liveability, flourishing and wellbeing for humans and non‐humans.